2013
DOI: 10.1186/1742-9994-10-80
|View full text |Cite
|
Sign up to set email alerts
|

Dogs are sensitive to small variations of the Earth’s magnetic field

Abstract: IntroductionSeveral mammalian species spontaneously align their body axis with respect to the Earth’s magnetic field (MF) lines in diverse behavioral contexts. Magnetic alignment is a suitable paradigm to scan for the occurrence of magnetosensitivity across animal taxa with the heuristic potential to contribute to the understanding of the mechanism of magnetoreception and identify further functions of magnetosensation apart from navigation. With this in mind we searched for signs of magnetic alignment in dogs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 33 publications
(34 reference statements)
1
39
0
1
Order By: Relevance
“…Consequently, although there is insufficient information to determine if the observed preference in wood mice is innate or learned, it appears likely that at least some component of the response is innate. Although the adaptive significance of spontaneous magnetic alignment remains an open question 8 44 45 46 , the widespread occurrence in epigeic mammals makes this response ideal for initial studies of the mechanism(s) of magnetoreception.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, although there is insufficient information to determine if the observed preference in wood mice is innate or learned, it appears likely that at least some component of the response is innate. Although the adaptive significance of spontaneous magnetic alignment remains an open question 8 44 45 46 , the widespread occurrence in epigeic mammals makes this response ideal for initial studies of the mechanism(s) of magnetoreception.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is reasonable to consider that there has been no convincing evidence for the magnetic compass that underlies the observed flies' horizontal orientations. Second, recent studies that showed magnetosensitive body alignment in two animal species (Bazalova et al ; Hart et al ) supported the possibility that animals can exhibit magnetoreceptive behavior by sensing changes in declination without detection of the direction of geographic north. Cockroaches could sense repeated changes in magnetic direction caused by the shift of the horizontal component of the GMF; they showed significant correlated body alignment within an interval of a few minutes without any geographic directional cue in the testing arena (Bazalova et al ).…”
Section: Discussionmentioning
confidence: 95%
“…The daily variation of declination reaches a few tenths of a degree even in the absence of solar disturbance (Finlay et al 2010;Thébault et al 2015). Although the scale of variation appeared to be very small, magnetosensitive animals such as dogs appeared to be able to detect such minute variation as described above (Hart et al 2013). If this also somehow happened in the fruit flies, they were probably able to use both the inclination and declination compasses at the same time.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Malkemper and others, proved the magnetic sensitivity in dogs. The conclusion of their paper states [41]: "magnetic sensitivity was proved in dogs, a measurable, predictable behavioural reaction upon natural MF fluctuations could be unambiguously proven in a mammal, and high sensitivity to small changes in polarity, rather than in intensity, of MF was identified as biologically meaningful". As we can see in Table 13, the magnetic anomalies of both declination and intensity of the FM occur suddenly and frighten the dogs, who do not see the "enemy" as when they see an intruder in their territory, but perceive the magnetic change with their magneto-sensitive receptors and are disoriented, just as the birds are also disorientated, and which in these moments can "make mistakes" in the direction of flight and go slamming into plants.…”
Section: The Magnetic Anomalies and Vocal Sequences Of Dogsmentioning
confidence: 99%